2010
DOI: 10.1007/s10750-010-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a top invertebrate predator (Dytiscus alaskanus; Coleoptera: Dytiscidae) on fishless pond ecosystems

Abstract: We investigated the predatory effects of Dytiscus alaskanus, a large predaceous diving beetle, on the biomass, species composition and diversity of fishless pond communities. The effects were tested using presence and absence treatments of D. alaskanus in 24 mesocosms distributed among six ponds. We sampled phytoplankton, zooplankton and macroinvertebrates every two weeks for a six week period. Periphyton was sampled from the mesocosm walls on the final day. Total macroinvertebrate biomass decreased in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…This is due in part to the importance this group in aquatic environments, both in abundance and diversity (Gray, 1981;Ramirez and Pringle, 1998;Stenert et al, 2004;Tupinambas et al, 2007;Paula and Fonseca-Gessner, 2010), as well as in the dynamics of aquatic systems, as part of the energy flow and nutrient dynamics (Larson, 1997;Peterson et al, 1999;Casatti et al, 2009;Vinnersten et al, 2009;Cobbaert et al, 2010). In recent years, water beetles have been gaining attention in monitoring programmes and environmental assessments, due to the sensitivity of some families to environmental change (Hilsenhoff, 1977;Ribera and Foster, 1992;Ribera, 2000;Garcia-Criado and Fernandez-Aláez, 2001;Compen and Céréghino, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the importance this group in aquatic environments, both in abundance and diversity (Gray, 1981;Ramirez and Pringle, 1998;Stenert et al, 2004;Tupinambas et al, 2007;Paula and Fonseca-Gessner, 2010), as well as in the dynamics of aquatic systems, as part of the energy flow and nutrient dynamics (Larson, 1997;Peterson et al, 1999;Casatti et al, 2009;Vinnersten et al, 2009;Cobbaert et al, 2010). In recent years, water beetles have been gaining attention in monitoring programmes and environmental assessments, due to the sensitivity of some families to environmental change (Hilsenhoff, 1977;Ribera and Foster, 1992;Ribera, 2000;Garcia-Criado and Fernandez-Aláez, 2001;Compen and Céréghino, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The numerous aquatic plants and low water depth here impede the access of fish to plankton, and for this reason crustaceans often concentrate in this microhabitat (Burks et al, 2001(Burks et al, , 2002Geraldes and Boavida, 2004), where invertebrate predators such as water bugs can effectively reduce the abundance of zooplankton. Other authors have confirmed that aquatic invertebrates can regulate the abundance of plankton in the case of limited feeding by fish (low depth, high macrophytes density or poor visibility) (Horpilla et al, 2009;Cobbaret et al, 2010). Hence zooplankton present in large numbers in the water/land zone may be a source of food for water bugs (Eitam and Blaustein, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…However, the distinction between large lakes and smaller lakes/larger perennial ponds is not always clear as the size of lentic freshwater bodies represents a gradient and 'comprises an environmental continuum without any clear delimitation' (Søndergaard et al, 2005: 144). Notwithstanding, Søndergaard et al (2005) has suggested that there are several factors that can separate larger lakes from smaller lakes/ponds; i) Ponds/smaller lakes often have a much greater littoral zone and closer contact with the surrounding terrestrial habitat which can result in a greater interaction between aquatic and terrestrial biota and matter (Søndergaard et al, 2005); ii) Smaller lakes and ponds typically have much smaller catchments than lakes (Davies et al, 2008a) resulting in more isolated and insular freshwater habitats compared to larger lakes with greater catchment areas and riverine inflows (Søndergaard et al, 2005); iii) Vertebrate predators (fish) are typically less well supported in ponds (Søndergaard et al, 2005); iv) In the absence of fish, macroinvertebrate predation is likely to increase in importance in smaller lakes and ponds, with predatory invertebrates potentially taking over the role of fish (Søndergaard et al, 2005;Cobbaert et al, 2010); v) Smaller lakes and ponds are typically much shallower and are protected from the wind which can enable submerged and floating macrophytes to cover large proportions of the pond surface area (Søndergaard et al, 2005); vi) Ponds/smaller lakes have a more heterogeneous habitat and physicochemical environment (e.g., greater littoral zone compared to lakes -increased structural complexity) which can provide a range of habitat niches for fauna to colonize . In addition, smaller lakes and ponds have relatively stagnant surface water compared to larger lakes which is favoured by certain freshwater taxa (Søndergaard et al, 2005) and; vii) Ponds and smaller lakes are almost always polymictic, with increased benthicpelagic coupling and a significantly greater influence and impact on water column nutrients from the sediment compared to larger lakes (Søndergaard et al, 2005).…”
Section: Pond or (Shallow) Lake: What's The Difference?mentioning
confidence: 99%
“…Invertebrate densities in submerged macrophyte beds were not influenced by fish indicating that macrophytes can act as refugia for invertebrate taxa (Gilinsky, 1984;Diehl, 1992). Within fishless ponds, Dytiscidae, Hemiptera and Odonata are top predators and can influence community structure by reducing macroinvertebrate richness and abundance at both local and metacommunity scales (Cadotte et al, 2006;Turner and Chislock, 2007;Cobbaert et al, 2010).…”
Section: Local (Physicochemical/biological) and Spatial (Connectivitymentioning
confidence: 99%